The association between sleep quality and anxiety symptoms: a cross-sectional study based on Tibetan university students at high altitude in China - Shi, Mengying; Miao, Ruijing; Bing, Meijun; Liu, Shiru (Frontiers in Psychology, 2025)
BackgroundThere have been more previous studies on sleep quality and anxiety symptoms among university students in plains areas. However, fewer studies have been conducted on Tibetan university students at high altitude. Analyzing the relationship between sleep quality and anxiety symptoms due to increased altitude may provide a reference for mental health promotion and intervention for Tibetan university students in high altitude areas.MethodsStratified whole cluster sampling was used. The pittsburgh sleep quality index (PSQI) scale was used to investigate the sleep quality of 4,777 university students at high altitude in China. The self-rating anxiety scale (SAS) was used to investigate anxiety symptoms. The chi-square test was used to compare the detection rates of anxiety symptoms among different groups, and logistic regression analysis was used to analyze the association between sleep quality and anxiety symptoms.ResultsThe prevalence of anxiety symptoms among Tibetan university students at high altitude in China was 25.7%. The detection rate of anxiety symptoms among girls (28.4%) was higher than that of boys (22.1%), and the difference was statistically significant (χ2 = 24.634, p < 0.001). The detection rates of anxiety symptoms among university students with sleep quality of “Good,” “Medium” and “Poor” were 1.8, 4.8 and 39.2%, respectively, and the differences were statistically significant (χ2 = 779.759, p < 0.001). Logistic regression analysis after adjusting for relevant covariates showed that the risk of anxiety symptoms was higher in the “Medium” (OR:3.479, 95%CI:1.946 ~ 6.221) and “Poor” (OR:44.817, 95%CI:29.175 ~ 68.847) groups, compared with the “Good” group. The same trend was observed in both men and women at the university level.ConclusionThere is a close relationship between sleep quality and the occurrence of anxiety symptoms among Tibetan university students at high altitude in China. Improving sleep quality may have a positive effect on reducing the occurrence of anxiety symptoms among Tibetan university students at high altitude.